Studi Pencemaran Udara Oleh Kendaraan Bermotor - D Karyadi (Balai Besar Kimia dan Kemasan, 1998)
Componen of air pollution from transportation consist of: CO, Nox, Sox, HC, paticles and Pb Br 2. Based on the result, of sawyer Research CO was formed at ER > 1, while NO was formed at ER < 1. Beside that sawyer also found that the combustion at low temperature, CO decreasing and prevented to form NO.For decreasing air pollution we must arrange the comparation of air and fuel. The other side we must also effort a good maintenance of machine and step by step to test the emission gas from the automobile. TEL additive must be subtituted with the other additive that it does not pollution.